Periodontal diseases and carotid intima‐media thickness in Bangladesh. (12th August 2016) - Wu, Fen; Chen, Yu; Demmer, Ryan T.; Parvez, Faruque; Paul, Rina Rani; Shaheen, Ishrat; Sarwar, Golam; Ahmed, Alauddin; Eunus, Mahbub; Ahsan, Nafiz; Habibullah, Nur Mohammad; Islam, Tariqul; et al.
Abstract: Aim: To evaluate the relationship between periodontal diseases and subclinical atherosclerosis in a younger and lean South Asian population. Methods: We conducted a cross‐sectional study in 917 subjects (mean age 46 years and mean body mass index 21.1 kg/m 2 ) from the Health Effects of Arsenic Longitudinal Study in Bangladesh. Multivariate linear regression models were used to assess the associations between multiple clinical measures of periodontal diseases and carotid intima‐media thickness (IMT). Results: Mean attachment loss (AL) and percentage of sites with AL ≥ 4 mm (% AL ≥ 4) were associated with increased IMT. The IMT was 20.0‐ μ m (95% CI: 2.2, 37.8) and 26.5‐ μ m (95% CI: 8.9, 44.1) higher in subjects in the top quartile of mean AL (>3.72 mm) and % AL ≥ 4 (>58.4%), respectively, compared to those in the bottom quartile. In a subset of 366 subjects, mean AL was positively associated with plasma levels of matrix metalloproteinase‐9 ( p < 0.05) and soluble intercellular adhesion molecule‐1 ( p < 0.01). Conclusions: Attachment loss was associated with subclinical atherosclerosis in this young and lean Bangladeshi population. Future prospective studies are needed to confirm this association.